2001
DOI: 10.1016/s0014-5793(00)02433-9
|View full text |Cite
|
Sign up to set email alerts
|

Disulfide bridge reorganization induced by proline mutations in maurotoxin

Abstract: Maurotoxin (MTX) is a 34-residue toxin that has been isolated from the venom of the chactidae scorpion Scorpio maurus palmatus, and characterized. Together with Pi1 and HsTx1, MTX belongs to a family of short-chain four-disulfidebridged scorpion toxins acting on potassium channels. However, contrary to other members of this family, MTX exhibits an uncommon disulfide bridge organization of the type C1^C5, C2Ĉ6, C3^C4 and C7^C8, versus C1^C5, C2^C6, C3^C7 and C4Ĉ 8 for both Pi1 and HsTx1. Here, we report that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 14 publications
0
25
0
Order By: Relevance
“…However, MTX is able to adopt the standard C1-C5, C2-C6, C3-C7, and C4-C8 arrangement (as observed in other ␣-KTx6 members) consecutive to selective amino acid residue substitution(s) (16 -18). The latter concerned Lys 15 , Gly 33 (18), or Pro 12 and Pro 20 (17) of MTX and were found to markedly affect peptide affinities toward the various K ϩ channel subtypes. Though the substituted residues were mainly selected on the basis of a pre-* This work was supported by CNRS, INSERM, the Commissariat à l'Energie Atomique, and Cellpep S.A.…”
Section: Maurotoxin (Mtx)mentioning
confidence: 99%
“…However, MTX is able to adopt the standard C1-C5, C2-C6, C3-C7, and C4-C8 arrangement (as observed in other ␣-KTx6 members) consecutive to selective amino acid residue substitution(s) (16 -18). The latter concerned Lys 15 , Gly 33 (18), or Pro 12 and Pro 20 (17) of MTX and were found to markedly affect peptide affinities toward the various K ϩ channel subtypes. Though the substituted residues were mainly selected on the basis of a pre-* This work was supported by CNRS, INSERM, the Commissariat à l'Energie Atomique, and Cellpep S.A.…”
Section: Maurotoxin (Mtx)mentioning
confidence: 99%
“…MTX Pi1 blocks, effectively Shaker B K + , outward currents with higher affinity than MTX7. Besides obtaining this analog through Tyr 32 modification, we also observed that similar shifts in half‐cystine pairings could be produced by introducing selected point mutations in MTX amino acid sequence8–10. The MTX Pi1 pattern is the native pattern of the MTX‐related toxin, such as Pi111 and HsTx112, both short‐chain four disulfide‐bridged scorpion toxins sharing a high degree of sequence identity with MTX (from 53% to 68%).…”
Section: Introductionmentioning
confidence: 74%
“…The two Pro residues were chosen because of the structural constraints they induce in the MTX structure, suggesting that they were susceptible to influence MTX disulfide bridge pattern. As a matter of fact, the double mutation Ala 12 and Ala 20 was shown to produce the Pi1‐like disulfide bridging10. Gly 33 was chosen because of its strategic location between Cys 31 and Cy 34 , also suggesting its potential involvement in the formation of this peculiar disulfide bridge.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this case, the disulfide-pairing arrangement and consequent conformation of maurotoxin, a 34-mer potassium channel blocker isolated from scorpion venom, was shown to be drastically influenced by the presence of proline residues [85]. Despite possessing a conserved cysteine framework of the four-disulfide-bridged scorpion toxin, maurotoxin adopts a novel cysteine-pairing pattern (C1-C5, C2-C6, C3-C4, and C7-C8) that is distinct from the classical cysteine-pairing framework (C1-C5, C2-C6, C3-C7, and C4-C8) seen in Pi1 and HsTx1 toxins, the other two members of the same family.…”
Section: Imino Acid Prolinementioning
confidence: 99%